A nonsense mutation causes hereditary goitre in the Afrikander cattle and unmasks alternative splicing of thyroglobulin transcripts. - Ricketts, M H (1987)
The hereditary goitre of Afrikander cattle is an autosomal recessive disease characterized in homozygotes by the production of abnormal thyroglobulin (Tg) and the coexistence in the thyroid of normal-sized 8.4-kilobase (kb) Tg mRNA with a misspliced 7.3-kb message having lost exon 9. We have cloned and sequenced the cDNA segment corresponding to the abnormal exon 8-exon 10 junction and the relevant genomic DNA region. The mutation responsible for the disease is a cytosine to thymine transition creating a stop codon at position 697 in exon 9. The original reading frame is maintained in the 7.3-kb mRNA, which, as it lacks the mutated exon, is translatable into a potentially functional protein. This puzzling phenotype in which a mutated exon is apparently removed selectively from transcripts by alternative splicing leads us to suggest that the 7.3-kb transcript could be present in normal animals. Using a sensitive oligonucleotide hybridization assay, we have demonstrated that a 7.3-kb mRNA lacking exon 9 does exist in normal thyroids as a minor mRNA species. As it is fully translatable, the 7.3-kb mRNA is expected to be more stable than the normal-sized 8.4-kb message. This probably accounts for the higher proportion of 7.3-kb transcript found in the goitre.